Current challenges in imaging the mechanical properties of tissue engineered grafts - Luo, Lu; Okur, Kerime Ebrar; Bagnaninchi, Pierre O.; El Haj, Alicia J. (Frontiers in Biomaterials Science, 2024)
The mechanical performance of tissue-engineered grafts is crucial in determining their functional properties, integration with native tissue and long-term repair outcome post-implantation. To date, most approaches for testing the mechanical properties of tissue-engineered grafts are non-sterile and invasive. There is an urgent need to develop novel sterile approaches for online monitoring mechanical properties of engineered tissues in order to ensure these engineered products meet the desired mechanical strength prior to implantation. In this paper, we overview various approaches for mechanical testing of engineered tissues, which span from traditional methods to medical imaging concepts in magnetic resonance elastography, ultrasound elastography, and optical coherence elastography. We focused on the applicability of these methods to the manufacturing of tissueengineered products online e.g., if such approach provides a sterile monitoring capacity and is capable of defining mechanical heterogeneity in engineered tissues throughout their growth in vitro in real-time. The review delves into various imaging modalities that employ distinct methods for inducing displacement within the sample, utilizing either strain-based or shear wave-based approaches. This displacement can be achieved through external stimulation or by harnessing ambient vibrations. Subsequently, the imaging process captures and visualizes the resultant displacement. We specifically highlight the advantages of novel non-invasive imaging methods such as ultrasound elastography and optical coherence elastography to assess the mechanical properties of engineered tissues in vitro, as well as their potential applications in cancer study, drug screening and the in vivo evaluation of the engineered tissues.